The contributions of organisational agility towards business performance within small and medium scale enterprises in Gauteng province - Govuzela, Sithembiso (My University, 2018)
Only one in ten newly established business enterprises survive for longer than ten years in the business environment. The reasons behind the failures of these small enterprises include the lack of access to financing, lack of financial and managerial skills, lack of expertise, as well as economic factors such as poor sales and weak growth prospects. The new norm in industry requires organisations to have a remarkable amount of agility to survive and succeed. This is important in South African SMEs given their significant contributions to the national economy. A major research gap exists, which pertains to the scant evidence of studies that focus on the influence of organisational agility on business performance of small to medium enterprises in South Africa. The purpose of this study is to investigate the influence of organisational agility on business performance in small to medium enterprises in the Gauteng province. Using a quantitative approach and a cross-sectional survey research design, a structured questionnaire was administered to 564 randomly selected owner-managers of small to medium enterprises in the Gauteng province. Questionnaire items were adapted from previously validated scales. Simple descriptive statistics in the form of percentages and mean scores were utilised in testing the perceptions of respondents towards organisational agility, its sub-elements and business performance. Hypotheses were tested using the structural equation modelling approach, which was conducted after implementing a confirmatory factor analysis to test the psychometric properties of the measurement scales. The results of the study show that owners and managers of small and medium enterprises perceived that the performance of their organisations was satisfactory in terms of technology capability, collaborative innovation, organisational learning, internal alignment, organisational agility and business performance. Upon testing the hypotheses, positive and significant relationships were observed between organisational agility and its four dimensions, namely technology capability, collaborative innovation, organisational learning and internal alignment. In turn, organisational agility exerted a significant and positive influence on business performance. The results of the study imply that the performance of small to medium enterprises can be improved significantly through adjustments to organisational agility and its subdimensions. This study is important in that its results can be applied to assist small to medium enterprises to survive and succeed in today’s turbulent and tomorrow’s dynamic operational environments, where agile organisational abilities are required.
D. Tech (Department of Human Resource Management, Faculty of Management Sciences), Vaal University of Technology.
Keywords: business enterprises, financing, finance, organisational agility, business performance; Organizational change.; Organizational effectiveness -- Gauteng (South Africa).; Business enterprises -- Gauteng (South Africa).